The intended tasks of military formations, units and subunits of Interior Troops in peacetime opportunities evaluation method - Tsys, О. І. (Honor and Law, 2019)
The method and algorithm of intended tasks of military formations, units and subunits of Interior Troops in peacetime opportunities evaluation are considered to justify recommendations for decision-making of service fighting actions.